The Public/Private Mix in the Income Package of the Elderly: A Comparative Study - Juergen K. Kohl (Luxembourg Income Study (LIS), 1992)
A comparative study of income of the elderly in four industrialized countries using LIS data sets. Emphasis was placed on analyzing elderly income from a perspective of household income, or the whole 'income package' of family households, thus allowing for evaluation of impact of differing benefit levels and benefit structures on the economic status of the elderly.
Keywords: 330; Deutschland; Großbritannien; Schweden; Schweiz; Alte Menschen